Development of an Improved Network Security System using Firewall for Securing Organisational Data - Ele, Bassey; E. E., Umoh,; D. O., Egete, (Discoveries in Agriculture and Food Sciences, 2020)
It is eminent that the Internet is far from being secure. Insecure networks have caused organizations to lose lots of money as a result of data loss or data corruption, and even worse, some organizations have also lost their reputation hence reduce the client’s confidence. Therefore, this research focused on the development of an improved network security system using a firewall that can secure both the internal and external network of an organization. The system was developed using both packet filtering and proxy server architectures to prevent unauthorized connection or access to the organization server or resources thereby reducing the risk of attacks to the network and loss of organizational data. The system was implemented using PHP and python programming languages and the backend was developed using MySQL as the database server; HTML, CSS, and JavaScript for the frontend layout. The implementation of this firewall system includes a monitoring admin interface from where most activities within the private network can be monitored and also this system can prevent or deny the unauthorized request of services either by an intruder from an external network or personnel within the network. Based on the findings of this study, the developed system is recommended for any organization that depends on computer networks for the running of their daily activities.